A study of customers' satisfaction towards service quality in Gadek Hot Spring / Mohd Izzat Azim Arrifin , Nur Hidayah Mohamad and Rozaira Rashidi - Azim Arrifin, Mohd Izzat; Mohamad, Nur Hidayah; Rashidi, Rozaira (Faculty of Hotel and Tourism Management, 2013)
As people have the awareness of the benefits of natural hot spring it makes them travel from their origin to another destination just because to experience by themselves. Even in Malaysia itself there is only 7 natural hot spring that been discover and become one of the tourist attraction. One of it is Gadek Hot Spring that located in Alar Gajah, Melaka. People that staying near with Melaka usually will comes and enjoy the hot spring. Moreover, travellers from abroad also come to Gadek Hot Spring. From the benefit that it provides it make people come but the factor that makes people keep coming is the service quality that Gadek Hot Spring provided. It includes of the facilities, ticket price, appearance of the staff and others. In order to discover about whether customers satisfy with the service quality provided, researcher conducting a survey on this place. The objective of this study is to investigate customer satisfaction towards Gadek Hot Spring service quality